THE INFLUENCE OF GREEN INVESTMENT, LIQUIDITY, PROFITABILITY, AND FINANCIAL DISTRESS ON FIRM VALUE IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Zyanda Ayu Fiansyah; Vidya Ayu Diporini (Universitas Mercu Buana, 2026)
This study aims to analyze the influence of green investment, current ratio (CR), return on assets (ROA), and financial distress on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The population in this study was 89 companies and the sample used in this study was 17 companies selected through purposive sampling. Data were collected from the companies annual financial reports from the IDX website and PROPER Decree letters from the Ministry of Environment and Forestry website. The method used in this study is quantitative research. Data analysis was conducted using panel data regression with the random effect model, processed by Eviews 13. The results show that, simultaneously, all variables have an effect on firm value. However, partially, green investment and profitability (ROA) have no significant effect, while liquidity (CR) and financial distress have a significant negative effect on firm value.